Characteristics of filgrastim consumption in the oncology service of the Ramiro Priale Priale Hospital EsSalud. - Nuñez Julcarima, Maribid Kely (2020)
Objective: Yo determine the characteristics of service consumption of Filgrastim Oncology Hospital Ramiro Priale Prialé of EsSalud. Material and Methods:It is a descriptive, retrospective study and cross-section, using a sample of 144 cases of consumption of Filgrastim; using as documentary analysis technique and instrument data collection sheet. Results: The prevalence of use of filgrastim in clinical practice in the service of Oncology the Hospital Ramiro Priale Prialé of EsSalud, was 100%, with a consumption according to age, between ranges from 68 to 77 years, mostly in the female sex, with monthly average of consumption of 52.31 units and annual average cost of 94,221.6 and monthly 7851.80 new soles. Conclusions: Consumption of Filgrastim 300mg, was higher in women and older patients, highlighting the lymphoma non-Hodgkin’s diffuse diagnosis for consumption and is required for your prescription management guidelines to be implemented.